2012
DOI: 10.1063/1.4704752
|View full text |Cite
|
Sign up to set email alerts
|

Hofmeister effects in micromolar electrolyte solutions

Abstract: Ions induce both specific (Hofmeister) and non-specific (Coulomb) effects at aqueous interfaces. More than a century after their discovery, the origin of specific ion effects (SIE) still eludes explanation because the causal electrostatic and non-electrostatic interactions are neither local nor separable. Since direct Coulomb effects essentially vanish below ∼10 μM (i.e., at >50 nm average ion separations in water), we decided to investigate whether SIE operate at, hitherto unexplored, lower concentrations. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 77 publications
(118 reference statements)
7
68
0
Order By: Relevance
“…We have previously suggested that the closer approach of the larger ions to air-liquid interfaces could be the outcome of the actions of a repulsive (toward the interface) force, f rep , a net attractive force, f atr , due the unbalanced dispersive forces exerted by the whole liquid on interfacial layers, i.e., those accounting for macroscopic liquid cohesion (see Appendix S2 in the supplementary material 67 ), 11,[39][40][41] and the negative entropy of mixing associated with the creation of interfacial concentration gradients. The essential point for present purposes is that anion concentration profiles should peak at different depths, z = 1 − δ, depending on their ionic radii.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously suggested that the closer approach of the larger ions to air-liquid interfaces could be the outcome of the actions of a repulsive (toward the interface) force, f rep , a net attractive force, f atr , due the unbalanced dispersive forces exerted by the whole liquid on interfacial layers, i.e., those accounting for macroscopic liquid cohesion (see Appendix S2 in the supplementary material 67 ), 11,[39][40][41] and the negative entropy of mixing associated with the creation of interfacial concentration gradients. The essential point for present purposes is that anion concentration profiles should peak at different depths, z = 1 − δ, depending on their ionic radii.…”
Section: Resultsmentioning
confidence: 99%
“…We investigate χ for different (X − /Y − ) anion pairs in four solvents as functions of gas velocity, ν G , and third anion (Z − ) additions in the 0.1-100 μM range. 11 Detailed descriptions of our experimental setup have been presented before. [20][21][22] Here, we summarize the key events that give rise to our mass spectral signals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that different anions populate interfacial layers at depths that are inversely correlated with their relative surface affinities (63). The emerging picture is that surface affinities indicate how close anions approach the interface rather than their relative concentrations within a single subsurfacial layer.…”
Section: Quantum-mechanical Calculationsmentioning
confidence: 99%
“…Electrospray mass spectrometry also provides evidence for an enhancement of hydronium [75] and a depletion of hydroxide [76] at the air-water interface.…”
Section: Spectroscopymentioning
confidence: 99%